The 23rd IEEE International Symposium on Robot and Human Interactive Communication 2014
DOI: 10.1109/roman.2014.6926375
|View full text |Cite
|
Sign up to set email alerts
|

Shut up and play: A musical approach to engagement and social presence in Human Robot Interaction

Abstract: With a view to studying the development of social relationships between humans and robots, it is our contention that music can help provide extended engagement and open ended interaction. In this paper we explore the effectiveness of music as a mode of engagement using Mortimer, a robot able to play a drum kit and employing a composition algorithm to respond to a human pianist. We used this system to conduct a comparative study into the effects of presenting the robot as a social actor or as an instrument. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Unlike our previous study, where all but one of the sessions were of equal length [23], the length of sessions ranged from the minimum of 20 minutes right up towards the maximum of 45. As such, the measure of tracks per session used previously is confounded by this variable and not a particularly elucidating one when attempting to investigate the smoothness and immersion of the participant's playing.…”
Section: Methodsmentioning
confidence: 66%
See 4 more Smart Citations
“…Unlike our previous study, where all but one of the sessions were of equal length [23], the length of sessions ranged from the minimum of 20 minutes right up towards the maximum of 45. As such, the measure of tracks per session used previously is confounded by this variable and not a particularly elucidating one when attempting to investigate the smoothness and immersion of the participant's playing.…”
Section: Methodsmentioning
confidence: 66%
“…We examine the number of button stops, as opposed to allowing tracks to finish naturally or due to silence, as our earlier work had indicated that those in the reduced social condition used the tablet to explicitly stop the robot more than the those who experienced Mortimer presented as a social actor [23]. They also found that framing the study as a social interaction, and so dividing the session into social and musical interactions, increased both engagement and social presence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations